Đào tạo nghề đáp ứng chiến lược Tăng tốc đầu tư tại Khu kinh tế Dung Quất - Nguyen, Văn Anh (Journal of Technical Education Science, 2007)
The Vietnam middle region industry is increasing to catch up with the development of our country. Dungquat economic zone is region’s development impetus. With important achievement made in socio-economic development in recent years, promotion of vocational training is deemed as a fundamental solution to increase the number of technical workers to meet the demand of the Dungquat businesses